Developmentally appropriate patient education during transition: A study of healthcare providers' and parents' perspective. (June 2020) - Morsa, Maxime; Gagnayre, Rémi; Pomey, Marie-Pascale; Deccache, Carole; Lombrail, Pierre
Introduction: Patient education is recommended to improve the transition from paediatric to adult care for young people with chronic conditions. But a consensus has not been reached regarding a particular model. This study aimed to understand how to prepare for the implementation of a Developmentally Appropriate Patient Education during Transition (DAPET), which would revolve around the young person's psychosocial development. Method: Three focus groups were organised with healthcare providers and two focus groups took place with the parents of young people with chronic conditions. We used activity theory to explore practices and to identify obstacles to the implementation of DAPET, as well as to recognise which resources might be available to implement DAPET. Results: Healthcare providers agreed on the need to engage in an educational approach centred on the psychosocial development of young people during transition. However, study findings highlight the following obstacles to doing so: a lack of competencies in adolescent and young adult medicine and a lack of available resources to meet these goals. Furthermore, parents wanted to redefine their role in the transition process and to allow their children to develop self-management skills. Conclusion: Healthcare providers and parents considered the implementation of DAPET to be acceptable and even advisable. However, the programme's feasibility was questioned due to perceived shortfalls in the hospital system as it currently stands and the ways in which an educational approach would be applied. An environment that facilitates healthcare providers' educational initiatives and encourages the participation of parents is required.